Empowering Women of 'Aisyiyah Wonosari in Preventing Microplastics Impacts on Reproductive Health - Rozifa, Annisa' Wigati; Novembriani , Rizqie Putri; Yumni , Fathiya Luthfil (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
Microplastics have emerged as a significant threat to human health, particularly affecting the female reproductive system. This community service program aimed to increase the knowledge of ‘Aisyiyah Members in Wonosari, Bondowoso, about the dangers of microplastics and to encourage the adoption of a healthy and environmentally friendly lifestyle. The program employed a participatory, community-based approach that included socialization, education, and training sessions focusing on reproductive health and household waste management. The team employed interactive methods, including PowerPoint presentations, posters, and guidebooks, to enhance engagement and foster a deeper understanding. They implemented a pre- and post-test design to measure the improvement in knowledge among 51 participants. The results showed an 80% increase in participants' knowledge regarding the dangers of microplastics and their impacts on reproductive health. The establishment of the "Emak EcoCare" community further ensured program sustainability by empowering women as environmental cadres to promote waste sorting and healthy lifestyle practices. This program demonstrated that community-based education can effectively raise awareness and foster behavioral change in managing household waste and reducing microplastic exposure. Continued mentoring and replication are recommended to ensure the long-term sustainability of these efforts.